A putative structural variant and environmental variation associated with genomic divergence across the Northwest Atlantic in Atlantic Halibut. (1st August 2021) - Kess, Tony; Einfeldt, Anthony L; Wringe, Brendan; Lehnert, Sarah J; Layton, Kara K S; McBride, Meghan C; Robert, Dominique; Fisher, Jonathan; Le Bris, Arnault; den Heyer, Cornelia; Shackell, Nancy; Ruzzante, Daniel E; et al.
Abstract: Characterizing the nature of genetic differentiation among individuals and populations and its distribution across the genome is increasingly important to inform both conservation and management of exploited species. Atlantic Halibut ( Hippoglossus hippoglossus) is an ecologically and commercially important fish species, yet knowledge of population structure and genomic diversity in this species remains lacking. Here, we use restriction-site associated DNA sequencing and a chromosome-level genome assembly to identify over 86 000 single nucleotide polymorphisms mapped to 24 chromosome-sized scaffolds, genotyped in 734 individuals across the Northwest Atlantic. We describe subtle but significant genome-wide regional structuring between the Gulf of St. Lawrence and adjacent Atlantic continental shelf. However, the majority of genetic divergence is associated with a large putative chromosomal rearrangement (5.74 megabases) displaying high differentiation and linkage disequilibrium, but no evidence of geographic variation. Demographic reconstructions suggest periods of expansion coinciding with glacial retreat, and more recent declines in N e . This work highlights the utility of genomic data to identify multiple sources of genetic structure and genomic diversity in commercially exploited marine species.